A new look at Crocodylopodus meijidei: implications for crocodylomorph locomotion. Issue 5 (30th March 2022) - Castanera, Diego; Pascual-Arribas, Carlos; Canudo, José Ignacio; Puértolas-Pascual, Eduardo
ABSTRACT: A review of the type material of the crocodylomorph ichnotaxon Crocodylopodus meijidei Fuentes Vidarte and Meijide Calvo, 2001 from the Berriasian of Spain is carried out. The review allows a better characterization of this type ichnotaxon and provides interesting new data on the candidate trackmakers and especially on their locomotion. Three different size classes possibly related to different ontogenetic states or sexual dimorphism of the same small- to medium-sized crocodylomorph trackmaker are distinguished. Morphological differences within the sample such as digital impression lengths might be a consequence of differences in allometric growth, assuming similarities with extant crocodylians. Other differences are a consequence of variation in the morphological quality and mode of preservation across the sample. Some trackway features (intermediate-gauge trackways with high pace angulation, absence of tail, belly or drag marks) indicate the trackmakers, presumed neosuchian crocodylomorphs, were walking in a 'high-walk' mode with a semi-erect posture at a moderate speed. The trackmaker may have walked with more erect limb posture and with the center of mass located more anteriorly than occurs in extant species, albeit not as erect as quadrupedal animals such as mammals or other extinct archosaurs including trackmakers of other crocodylomorph ichnotaxa (e.g., Batrachopus ).